1993
DOI: 10.1128/aac.37.3.566
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity and beta-lactamase stability of FK-037, a parenteral cephalosporin

Abstract: The in vitro activity of FK-037, 5-amino-2-[[(6R, 7R)-7-[[(Z)-2-(2-amino-4-thiazolyl)-2-(methoxyimino) acetyl] aminol-2-carboxy-8-oxo-5-thia-1-azabicyclo[4.2.0]oct-2-en-3-yllmethyl1-1-(2-hydroxyethyl)-lH-pyrazolium hydroxide, inner salt, sulfate (1:1), a new parenteral cephem, was compared with those of cefepime, ceftazidime, imipenem, and ciprofloxacin. FK-037 inhibited methicillin-susceptible staphylococci at c4 jig/ml. Of 98 isolates of homogenous methicillin-resistant Staphylococcus aureus, 55 (56.1%) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
17
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 4 publications
2
17
1
Order By: Relevance
“…While recent animal model studies suggest that piperacillin-tazobactam may have an effective role in the treatment of infections caused by such strains, further investigations regarding the optimum dosing level of this agent are (17,31). Although previous reports of the activity of cefepime against ESBL producers have been contradictory (3,13,20,23,34,37), we found cefepime activity to be comparable to that of cefotaxime and aztreonam. On the basis of the level of activity and inoculum effect data, cefepime appears to have limited potential against such resistant strains.…”
contrasting
confidence: 44%
“…While recent animal model studies suggest that piperacillin-tazobactam may have an effective role in the treatment of infections caused by such strains, further investigations regarding the optimum dosing level of this agent are (17,31). Although previous reports of the activity of cefepime against ESBL producers have been contradictory (3,13,20,23,34,37), we found cefepime activity to be comparable to that of cefotaxime and aztreonam. On the basis of the level of activity and inoculum effect data, cefepime appears to have limited potential against such resistant strains.…”
contrasting
confidence: 44%
“…The agents tested were: ciprofloxacin (Miles Pharmaceuticals, West Haven, USA); levofloxacin, ofloxacin and FK-037 (Neu, Chin & Huang, 1993) RFLP of chrDNA was determined using the procedure previously used for Pseudomonas aeruginosa (Sader et al, 1993). After growing the cells in trypticase soy broth to the exponential phase, they were pelleted by centrifugation, washed and mixed with 2% agarose (SeaPlaque GTG, FMC, Rockland, USA) to a final 1% agarose concentration.…”
Section: Methodsmentioning
confidence: 99%
“…FK-037 has also been reported to have a broad spectrum of activity against gram-negative bacilli, including members of the family Enterobacteriaceae and Pseudomonas aeruginosa, and to be active against many ceftazidime-resistant isolates of Citrobacter spp., Enterobacter spp., and P. aeruginosa (2, 4-7, 11, 13, 16). Fu et al (2), Neu et al (14), and Nishino et al (15) have also demonstrated the activity of this compound against isolates of streptococci, including beta-hemolytic groups and Streptococcus pneumoniae, and Haemophilus influenzae. FK-037 has also been shown to be active against a variety of anaerobic bacteria other than the Bacteroides fragilis group (9).…”
mentioning
confidence: 99%
“…Data presented in abstracts in 1991 and 1992 suggested that FK-037 was more active than currently available extended-spectrum cephalosporins against staphylococci, including methicillin-resistant strains (5,12,15); however, at four times its MIC, FK-037 reduced the number of CFU of methicillin-resistant Staphylococcus aureus by only 1 order of magnitude while vancomycin reduced the number of CFU by over 3 orders of magnitude in killing curve studies (1). In studies by Neu et al (14), 16 ,ug of FK-037 per ml inhibited 50% of the S. aureus isolates tested with oxacillin MICs of >16 ,ug/ml. FK-037 has also been reported to have a broad spectrum of activity against gram-negative bacilli, including members of the family Enterobacteriaceae and Pseudomonas aeruginosa, and to be active against many ceftazidime-resistant isolates of Citrobacter spp., Enterobacter spp., and P. aeruginosa (2, 4-7, 11, 13, 16).…”
mentioning
confidence: 99%